Evaluation of fetal breathing-related nasal fluid flow Doppler parameters in pregnant women with gestational diabetes mellitus - Yıldırım, Mesut; Kale, İbrahim; Çetinkaya, Osman Eren; Özel, Ayşegül (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
To investigate the fetal breathing-related nasal fluid flow Doppler parameters in pregnant women with gestational diabetes mellitus (GDM).This prospective, case-control study was conducted on a total of 90 pregnant women, including 44 with GDM and 46 with normal glucose tolerance. The control group was matched with the GDM group in terms of maternal age and gestational week. Fetal nasal fluid flow Doppler examination was performed between 32 and 34 weeks of gestation.Both groups were similar in terms of inspiration and expiration duration (p=0.809, p=0.710, respectively). Inspiration and expiration peak velocity were similar in both groups (p=0.444 and p=0.357, respectively). Inspiration duration/expiration duration and inspiration peak velocity/expiration peak velocity were similar in both groups (p=0.460, p=0.781, respectively). Both groups were similar in terms of total breathing duration and number of fetal breaths per minute (p=0.669, p=0.629, respectively). Postnatal respiratory distress syndrome (RDS) in newborns and neonatal intensive care unit (NICU) admissions were also similar in both groups (p=0.236, p=0.091, respectively).Although the sample size is limited, fetal breathing-related nasal fluid flow Doppler parameters appear to be unaffected in pregnancies with well-controlled GDM. Similar rates of neonatal RDS and NICU admissions between GDM and non-GDM groups support this finding. However, these findings are not yet applicable to clinical practice, as the study was limited to pregnant women with well-controlled GDM, and the impact of poorly controlled hyperglycemia on these parameters remains unknown. Further research is warranted to address this limitation.
Keywords: fetus; nasal fluid flow Doppler; gestational diabetes mellitus